2015
DOI: 10.1155/2015/614579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin Intake on Oxidative Stress Biomarkers in Male Reproductive Organs of Rats under Experimental Diabetes

Abstract: This study investigated the antioxidant system response of male reproductive organs during early and late phases of diabetes and the influence of melatonin treatment. Melatonin was administered to five-week-old Wistar rats throughout the experiment, in drinking water (10 μg/kg b.w). Diabetes was induced at 13 weeks of age by streptozotocin (4.5 mg/100 g b.w., i.p.) and animals were euthanized with 14 or 21 weeks old. Activities of catalase (CAT), glutathione-S-transferase (GST), glutathione peroxidase (GPx), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 76 publications
3
41
0
1
Order By: Relevance
“…Taken together, these phenomena may explain the significant reduction in GPx but not CAT in the present study, given that GPx may respond faster than CAT, particularly during the early stages of the disease. A recent study conducted by Gobbo et al [62] showed similar findings, with activation of GPx occurring early during the response to diabetes, whereas activation of CAT tended to occur at later stages of untreated diabetes. Further research is needed to understand the effects of PQ on GPx and CAT activities in the midbrain.…”
Section: Discussionsupporting
confidence: 52%
“…Taken together, these phenomena may explain the significant reduction in GPx but not CAT in the present study, given that GPx may respond faster than CAT, particularly during the early stages of the disease. A recent study conducted by Gobbo et al [62] showed similar findings, with activation of GPx occurring early during the response to diabetes, whereas activation of CAT tended to occur at later stages of untreated diabetes. Further research is needed to understand the effects of PQ on GPx and CAT activities in the midbrain.…”
Section: Discussionsupporting
confidence: 52%
“…Melatonin hidroksil radikali, superoksit radikali ve peroksinitrit gibi SOR türevlerini olarak ortadan kaldırarak direkt antioksidan etki gösterirken, endojen antioksidan enzimlerin yapımını artırarak indirekt olarak antioksidan etki de göstermektedir (21).…”
Section: Discussionunclassified
“…A similar trend of results is reported by Hamden et al (2008) using alloxan-induced T1DM rats. On the other hand, Gobbo et al (2015) have reported that DM did not significantly alter the testicular antioxidant defence system as shown by the insignificant alterations in the activities of antioxidant enzymes (SOD, CAT, GPx) and MDA level after 1 week and 8 weeks in STZ-induced T1DM rats.…”
Section: Testicular Oxidative Stressmentioning
confidence: 90%
“…Several studies using STZ-induced T1DM animal model have shown decreased daily sperm production, sperm count and motility (Suresh and Prakash, 2012;Gonzales et al, 2013), and increased percentage of spermatozoa with abnormal morphology (Kanter et al, 2013). Studies using alloxan-induced T1DM animal models (Hafez 2010;Ghlissi et al, 2012) have also yielded similar results.…”
Section: Effect Of Diabetes Mellitus On Spermatogenesismentioning
confidence: 99%
See 1 more Smart Citation